Critical success factors in the development of Malaysian Islamic marriage management system / Salahuddin Hamzah - Salahuddin , Hamzah (2022)
The aim of this research is to develop a framework depicting the critical success factors in developing an IT system in JAKIM and JAWI. Using quantitative methodology by distributing questionnaire to selected 63 officers and support staff of JAKIM and JAWI, the results were analysed using Relative Importance Indicator. The finding from this research shows that the dominant critical success factor is “human management” factor. Although system development project management is a highly technical project, the “human factor” in project management exerts the most important factor. The importance of leadership/top management or the “human aspect” in project management has been repeated by many researchers. The finding of this research have proven that in a hierarchical governmental organisation, the human aspect of leadership/top management, combined with user’s competencies and the availability of financial resources are the critical factors needed for success. This research has contributed in the understanding of officers and support staff of JAKIM and JAWI in acknowledging the critical factors that contributed to the success of the development of the system. Further improvement with regard to the aspect of top management, leadership and human management can be incorporated in the area of management training and career development of current and future government officers and not limited to those who are in project management related fields, but also other fields of management as well.